Separação espacial de fases no modelo de seis vértices - Passos, Ingryd Rodrigues dos (Universidade Federal de São Carlos, 2020)
In this work, we have studied the six-vertex model with domain wall and reflecting end boundary conditions, focusing mainly on the influence of boundary conditions on the thermodynamic limit. In order to find a complete analytical description for the so-called arctic curves, we have investigated three types of boundary correlations. These correlations were later used in two different methods designed to find the curves.
Spatial phase separation in the six-vertex model
Keywords: Modelo de seis vértices; Separação espacial de fases; Correlações na fronteira; Curvas árticas; Six-vertex model; Phase separation; Boundary correlations; Arctic curves; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::FISICA ESTATISTICA E TERMODINAMICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::METODOS MATEMATICOS DA FISICA